Thermoelectric Properties of Compacted Micro- and Nanodisperse Graphite Materials - I.M. Golev; V.N. Sanin (Журнал нано- та електронної фізики)
The experimental results of measuring the Seebeck coefficient S for carbon deposits containing multi-walled carbon nanotubes, compacted nanofibers, nano- and ultradisperse amorphous carbon are presented. The value of S for such kind of materials lies in the range of 7 to 60 V/K. It is indicated that a hopping conduction mechanism is typical of the compacted materials.